The prevalence, predictors, and criminogenic effect of joining a gang among urban, suburban, and rural youth. (December 2016) - Watkins, Adam M.; Taylor, Terrance J.
Abstract: Few empirical studies have focused on gang involvement outside urban areas. This study contributes to this sparse research by addressing three questions using a national sample: 1) are urban, suburban, and rural youth equally likely to report joining a gang; 2) are the predictors of joining a gang comparable for urban, suburban, and rural youth; and 3) does joining a gang have a similar effect on delinquency involvement for urban, suburban, and rural youth? Results indicate suburban and rural youth are just as likely as urban youth to report joining a gang; variables related to joining a gang among urban youth are largely related to joining a gang among suburban and rural youth; and joining a gang is just as criminogenic for suburban and rural youth as for urban youth. With the exception of finding that gang involvement is no less criminogenic for nonurban youth, results are consistent with the proposed hypotheses. Highlights: Little is known about youth gang membership in non-urban settings. Gang membership rates and their criminogenic effects are similar across settings. Context affects factors which lead youth to join gangs.